PENGARUH RASIO KEUANGAN TERHADAP HARGA SAHAM PADA PERUSAHAAN SEKTOR CONSUMER GOODS INDUSTRY: PENGARUH RASIO KEUANGAN TERHADAP HARGA SAHAM PADA PERUSAHAAN SEKTOR CONSUMER GOODS INDUSTRY - Widya Sari; Hendy Wijaya; Janny Franciska; Reny Octaviany Napitupulu (Jurnal Mantik, 2019)
The objective of this research is to analyze the influence of quick ratio, dividend per share, return on investment and debt to equity ratio on stock price in sector consumer goods industry listed in Indonesian Stock Exchange with the period of 2014-2018 partially or silmutaneouly. This research uses quantitative descriptive research. The population of this research are 38 companies and the number of sample is 9 companies. The results research of F test (simultaneous) showed that there is a significant influence between quick ratio, dividend per share, return on investment and debt to equity ratio on stock price in sector consumer goods industry listed in Indonesian Stock Exchange with the period of 2014-2018. The results research of T test (partial) showed that there is a significant influence dividend per share partially on stock price in sector consumer goods industry listed in Indonesian Stock Exchange with the period of 2014-2018.